KARAKTERISTIK PENDERITA SIROSIS HATI - Parlindungan Silaban, Bangun; Lumongga, Fitriani; Silitonga , Hendrika (Jurnal Kedokteran Methodist, 2020)
Background: Liver disease is a disease that still a health problem in both developed an developing countries. One of them is cirrhosis of liver which is a chronic liver disease at the end of progressive diffuse prosses of liver fibrosis characterized by distortion of the liver architecture and regenerative nodule formation and the cause is unknown with certainty. Method: This research method used was a literature review, using secondary data. Data were collected using documentation techniques. The research journlas used were 7 juornals with inclusion criteria for the publication date of the last 5 years, the language used in Indonesia or English, with the research subkects of patients diagnosed with liver cirrhosis, and full text publlication. Conclusion: characteristics of people with liver cirrhosis based on sex most often are male, the most common age group is 50-69 years, the history of hepatitis that causes liver cirrhosis is hepatitis B, the most common clinical symptom is acites, liver function test increassess are AST,ALT and total bilirubin, and the most common complication of liver citthosis is acites.